Diversity of Aquatic Macrophytes Vegetation in Tirunelveli, Tamil Nadu - Ramarajan, sekar; Saravana Ganthi, A. (Indian Forester, 2018)
The semi-arid districts of Tirunelveli consist of numerous irrigation tanks, interconnected by an ancient network of canals, and fed by the rivers originating from the Western Ghats. These tanks have good populations of aquatic flora. A detailed survey of aquatic macrophytes in selected tanks, Tirunelveli was made during the October-2014 to June -2015. A total of 50 species belonging to 21 family and 37 genera and 21 families are recorded in this tank. In selected tanks, perennial water source which serve as important gateways for the migratory waterfowl.